RANCANG BANGUN DAN MONITORING IP CAMERA B ERBASIS OPEN-WRT PADA KANTOR PDAM TIRTA BERKAH PANDEGLANG - Saleh Dwiyatno; Muhamad Rosi Sadi; Muhamad Natsir (Program Studi Sistem Informasi, Universitas Banten Jaya, 2019)
The development of CCTV technology makes it easier for a user in monitoring and monitoring a room or environment. But the lack of CCTV is a price that is still not reached by all levels of society. Because of this, it is necessary to build a new system that has the same features with CCTV tools in circulation but with a more affordable price.The new system is built by utilizing the openWRT operating system. The openWRT operating system will be installed on a wireless router with some additional tools to support its functionality such as speakers, soundcards, loudspeakers, webcam and flashdrive. The resulting system will have the ability to detect motion, the system is also capable of storing images, video and send snapshots via email when detected suspicious motion. In addition, this system also has some other features such as alarm alerts, motion detection scheduling so that its usage can be set as needed and easy access via internet so that can be accessed anywhere as long as connected to the internet